Effects of an Applied Workshop on Teacher Self-Efficacy and Intent to Teach Hydraulics - Johnson, Donald M.; Wardlow, George W. (Journal of Agricultural Systems, Technology, and Management, 2017)
Agricultural mechanics is an important component of school-based agricultural education programs, yet many university agricultural education programs lack the necessary facilities, personnel, and available credit hours to adequately prepare teachers in basic agricultural technologies, much less more advanced technologies. Technical workshops for inservice teachers may help fill this gap. This study investigated the effects of a one-day applied hydraulics workshop on teachers’ (n = 22) self-efficacy and intent to teach hydraulics. Prior to the workshop, a majority of teachers had a negative perception of their understanding of hydraulic concepts and their ability to teach hydraulics. Upon completion of the workshop, a majority of respondents had positive perceptions of their understanding of hydraulics concepts and their ability to teach hydraulics. Teachers’ participation in the workshop resulted in a statistically significant (p < .001) and large (Cohen’s d = 1.65) overall increase in self-perceived understanding and ability to teach hydraulics. In addition, the percentage of teachers indicating they planned to teach hydraulics in one or more courses increased from 36.4% prior to the workshop to 87.3% after the workshop.